Psychological analysis of mothers with cleft children - Rochmah, Yayun Siti; Putranto, Rama; Maryani, Intan (Odonto : Dental Journal, 2023)
Background: Parenting a child with cleft disorder required special attention, because this is related to the psychological condition of the mother. Mother's psychological problems can affect the growth and development of children. The purpose of this study was to analyze psychological of mothers with cleft children. Method: The research method used in this research is descriptive analytic method with purposive sampling approach. Methods of data collection using a questionnaire to measure parenting stress, the short form parenting stress index (PSI) had adopted from Adibin has been tested for validity and reliability. The number of samples in this study were 150 mothers with cleft lip, palatal and cleft lip/palatal children.Statistic analysis with ANOVA test and Spearman test Result: The results of this study indicate that there are differences in the stress levels of mothers of cleft children between cleft lips (CL), cleft palate (CP) and cleft lips and palate (CL/P) non syndromic (NS). The significance value is 0.000 (p